Homozygosity for a Robertsonian Translocation (13q;14q) in a Phenotypically Normal 44, XX Female with a History of Recurrent Abortion and a Normal Pregnancy Outcome - Miryounesi, Mohammad (J Reprod Infertil, 2016)
BACKGROUND: Robertsonian translocations are structural chromosomal abnormalities caused by fusion of two acrocentric chromosomes. In carriers of such translocations, different modes of segregations would result in the formation of either balanced (alternate segregation mode) or unbalanced (adjacent 1, adjacent 2, and 3:1 segregation modes) gametes. In addition, there is an increased risk for imprinting disorders in their offspring. Although it has been estimated that 1/1000 healthy persons carry a Robertsonian translocation, homozygosity for this type of structural chromosomal abnormality has been reported rarely. Most of reported cases are phenotypically normal but experience adverse pregnancy outcomes. CASE PRESENTATION: In this paper, a report was made on a normal female with a history of 4 consecutive first trimester fetal losses and a normal son referred to Center for Comprehensive Genetics Services, Tehran, Iran, in summer 2015. Cytogenetic analyses of proband and her infant showed 44, XX, der(13;14) (q10;q10)x2 and 45, XY, der(13;14)(q10;q10), respectively. Parents of proband have been shown to have 45, XY, der(13q;14q) and 45, XX, der(13q;14q) karyotypes, respectively. CONCLUSION: The present report was in agreement with the few reports of homozygosity for Robertsonian translocation which demonstrated normal phenotypes for such persons and possibility of giving birth to phenotypically normal heterozygote carriers of Robertsonian translocations.